2014
DOI: 10.3852/13-073
|View full text |Cite
|
Sign up to set email alerts
|

Multigene phylogenies of Ophiostomataceae associated with Monterey pine bark beetles in Spain reveal three new fungal species

Abstract: Ophiostoma species, some of which cause sapstain in timber and/or are mild pathogens, are common fungal associates of bark beetles (Coleoptera: Scolytinae). Three new Ophiostomataceae from Spain are recognized in the present study based on comparisons of sequence data for three gene regions as well as morphological characteristics. The new taxa are described as Ophiostoma nebulare sp. nov., Ophiostoma euskadiense sp. nov. and Graphilbum crescericum sp. nov.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 52 publications
(43 reference statements)
0
22
0
Order By: Relevance
“…The other four species from pine bark beetles come from single reports: S. rossi from the USA (Davidson 1971), S. aurorae from South Africa (Zhou et al. 2006), and two species from Spain (Romón et al., 2014a, Romón et al., 2014b). Interestingly, the S. gossypina complex is the only species complex in Sporothrix, apart from Lineage G, which includes species associated with conifer-infesting bark beetles.…”
Section: Discussionmentioning
confidence: 99%
“…The other four species from pine bark beetles come from single reports: S. rossi from the USA (Davidson 1971), S. aurorae from South Africa (Zhou et al. 2006), and two species from Spain (Romón et al., 2014a, Romón et al., 2014b). Interestingly, the S. gossypina complex is the only species complex in Sporothrix, apart from Lineage G, which includes species associated with conifer-infesting bark beetles.…”
Section: Discussionmentioning
confidence: 99%
“…The common practice of culturing specimens from insects and placement into phylogenetic trees obtained for the ITS region (e.g., Romon et al. ) already constitutes a useful framework for assessing the taxonomic diversity. The ITS marker exploits highly conserved primer recognition sequences for amplification, which reduces taxonomic bias, while the intervening central region is sufficiently variable for species‐level diagnostics.…”
Section: Discussionmentioning
confidence: 99%
“…Duong et al (2012) suggested that this species belongs to the Grosmannia serpens complex, but validation of the name will be possible only if the original material can be located . Other fungi in this group, Ophiostoma sejunctum (Villarreal et al 2005), Ophiostoma nebulare, Ophiostoma euskadiense and Graphilbum crescericum (Romón et al 2014) were described only very recently, suggesting that these fungi have been incompletely studied in the area.…”
Section: Introductionmentioning
confidence: 95%
“…Knowledge of the ophiostomatoid fungi in the Iberian Peninsula is very limited (De Ana Magán 1982;1983;Fernández et al 2004;Villarreal et al 2005;Romón et al 2007;Bueno et al 2010;Pestaña and Santolamazza-Carbone 2010;Romón et al 2014), and only three studies have dealt with their taxonomy. For example, a new species, Leptographium gallaeiciae, was described invalidly from stressed Pinus pinaster trees (De Ana Magán 1983).…”
Section: Introductionmentioning
confidence: 98%